Kesopanan Berkomunikasi Dalam Wawancara NCT Dream Bersama Ggondaehee - Siti Naimah; Nina Yuliana (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2024)
This study analyzes the language and behavioral politeness in the interaction between NCT Dream members Renjun and Jeno and host Ggondaehee on the show